Preservative Efectiveness Test of Dry Water Extract of Gambier (Uncaria Gambir Roxb.) In Cream Type of Cosmetics - fitri, Dewi Rahma; Prophet, Santy; Komarudin, Dede; Fatria Fajar, In Rahmi; Riyanto, Arief (Politeknik Kesehatan Kemenkes Jakarta II, 2023)
Gambier is an endemic plant that can grow properly such as in Indonesia it has been empirically used for natural coloring, antiinfection and burns wound healing. Gambier used as antimicrobials because its catechins compound. Catechins mechanism as antimicrobial are break the cell wall or cell membrane of bacteria, other mechanism is to precipitate of protein because the catechins properties is same with phenolic compound. This research aims to know the preservative effectivity of dry water extract of gambier (Uncaria gambir Roxb.) in cream type of cosmetics. Research methods are total plate count, yeast and mold count, logs and percentage of preservative effectivity test. The data of the result there are: gambier extract in Pseudomonas aeruginosa cream shows the preservative requirement at 2%, 2,5% and 3% concentrations with 100% of reduction and 3 logs reductions on 14th days testing; gambier extract in Staphylococcus aureus cream shows the preservative requirement at 3% concentrations with 100% of reduction and 3 logs reductions on 7th days of the test; gambier extract in Enterobacter aerogenes cream shows the preservative requirement at 2%, 2,5%, 3% and 3,5% concentrations with 100% of reduction and 3 logs reductions on 28th days of the test; gambier extract in Candida albicans cream shows the preservative requirement at 2%, 2,5% and 3% concentrations with 100% of reduction and 3 logs reductions on 7th days of the test; gambier extract in Aspergillus niger cream shows the preservative requirement at 2,5% and 3% concentrations with 100% of reduction and 3 logs reductions on 7th days of the test. Dry water extract of gambier has the potential that can be used as a microbial preservative in cream type of cosmetics